2014
DOI: 10.1267/ahc.14012
|View full text |Cite
|
Sign up to set email alerts
|

BOB.1-positive Classical Hodgkin’s Lymphoma Carries Hypermethylation of Its Promoter as Epigenetic Marker of Gene-silencing Memory

Abstract: Analysis of archival formalin-fixed, paraffin-embedded (FFPE) pathological specimens of three case of Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma (DLBCL) and three cases of classical Hodgkin lymphoma (CHL) revealed that hypermethylation of the BOB.1 gene promoter was exclusively observed in CHL. A discrepancy was observed, however, between the methylation status of the BOB.1 gene promoter and its expression in the EBV-positive mixed cellular CHL (MCCHL). Since MCCHL lacks the typical B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Subsequent analysis indicated that DNA methylation is directly involved in the control of some of these genes, while in case of others, the expression could be dependent on additional genetic encoding, i.e. some master transcription factors (69)(70)(71)(72)(73). Array-based genome-wide study of DNA methylation in HL cell lines (74) led to the identification of hypermethylation on 383 CpG islands, corresponding to 329 genes which were commonly associated with characteristic changes for germinal center derived B-cell lymphoma (gcdBCL).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Subsequent analysis indicated that DNA methylation is directly involved in the control of some of these genes, while in case of others, the expression could be dependent on additional genetic encoding, i.e. some master transcription factors (69)(70)(71)(72)(73). Array-based genome-wide study of DNA methylation in HL cell lines (74) led to the identification of hypermethylation on 383 CpG islands, corresponding to 329 genes which were commonly associated with characteristic changes for germinal center derived B-cell lymphoma (gcdBCL).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Immunohistochemistry enables us to describe protein expression in cells, but Watanabe et al [4] give a warning: protein expression does not always mean that a protein is really active. They had found not only high BOB.1 protein expression in HL but also hypermethylation of its promoter.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…But they are usually either weakly or partially expressed. This feature can be used in the differential diagnosis (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%